Assessment and analysis of voltage stability indices in power system network / Lee Liang Yoong - Lee, Liang Yoong (2019)
Voltage collapse is one of the major causes of nationwide blackout in recent years. Through the monitoring of power system, issues can be foresee and prevented. Voltage stability indices (VSI) has been proposed to be the monitoring and predicting tool for voltage stability due to its simplicity and fast calculation. These VSI are able to calculate the proximity of the voltage towards voltage collapse or determine a weak bus or line. However, many assumptions have been made in order to derive a simple bus system. As such there will be error subject to tolerance level and different characteristics. In this study, 8 VSI will be examined, consisting both line VSI & bus VSI. These VSI will be evaluated in IEEE-14 bus systems. The IEEE-14 bus will be tested under n-1-line contingency and load variation test conditions. The outcome of this study is to compare performance and suitability of each VSI. Line VSI is suitable to monitor transmission line, whereas bus VSI is suitable to monitor overall bus voltage stability. VSI should be used collectively to ensure reliability of a power system.